Inside and Outside Perspectives on Institutions: An Economic Theory of the Noble Lie - Cameron Harwick (Journal of Contextual Economics – Schmollers Jahrbuch, 2020)
If there exist no incentive or selective mechanisms that make cooperation in large groups incentive-compatible under realistic circumstances, functional social institutions will require subjective preferences to diverge from objective payoffs – a "noble lie." This implies the existence of irreducible and irreconcilable "inside" and "outside" perspectives on social institutions; that is, between foundationalist and functionalist approaches, both of which have a long pedigree in political economy. The conflict between the two, and the inability in practice to dispense with either, has a number of surprising implications for human organizations, including the impossibility of algorithmic governance, the necessity of discretionary rule enforcement in the breach, and the difficulty of an ethical economics of institutions. Leeson and Suarez argue that "some superstitions, and perhaps many, support self-governing arrangements. The relationship between such scientifically false beliefs and private institutions is symbiotic and socially productive" (2015, 48). This paper stakes out a stronger claim: that something like superstition is essential for any governance arrangement, self- or otherwise. Specifically, we argue that human social structure both requires and maintains a systematic divergence between subjective preferences and objective payoffs, in a way that usually (though in principle does not necessarily) entails "scientifically false beliefs" for at least a subset of agents. We will refer to the basis of such preferences from the perspective of those holding them as an "inside perspective," as opposed to a functionalist-evolutionary explanation of their existence, which we will call an "outside perspective." Drawing on the theory of cooperation, we then show that the two perspectives are in principle irreconcilable, discussing some implications of that fact for political economy and the prospects of social organization.
Keywords: C73; A13; 330; Game Theory; Cooperation; Institutions